32.7k views
21 votes
Um, ik i need help alot tonight lol

Um, ik i need help alot tonight lol-example-1
Um, ik i need help alot tonight lol-example-1
Um, ik i need help alot tonight lol-example-2
Um, ik i need help alot tonight lol-example-3
Um, ik i need help alot tonight lol-example-4
User Onosendi
by
6.0k points

1 Answer

4 votes

Answer:

See below

Explanation:


\frac{ {x}^(4) }{ {x}^( - 3) {y}^(0) } = \frac{ {x}^(4 + 3) }{ {y}^(0) } = \frac{ {x}^(7) }{1} = {x}^(7) \\ \\ 2 {x}^( - 3) = \frac{2}{ {x}^(3) } \\ \\ {( {x}^( - 3) )}^(8) = {x}^( - * 8) = {x}^( - 24) = \frac{1}{ {x}^(24) }

User Wuwucat
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.